(untitled) (Journal of Educational Sciences, 2017)
The article focuses on the role of education in the revival and strengthening of ethnocultural identity in today’s «national renaissance». The author considered cybernetic and synergetic model of society development network structures. Education is the way a person entering the world of national and world culture and is playing a constructive role in the development of his cultural identity. In today’s globalization, a person must have significant competences in foreign languages and international culture and the culture of the country. To one of today’s requirements commensurate general education is the need to trilingualism. In the cultural identity of the modern citizen are two interrelated Plast – ethnic identity, as the representative of one ethnic and supra-ethnic Kazakh identity. And within ethno-cultural identity has features associated with zhuzes and tribal identity, and linguistic identity (Kazakhspeaking and Russian-speaking Kazakhs). In the discourse of the Kazakhstan philosophers speak out reflections on the distinction between Kazakh and Kazakh civilization. An important place in the policy of education of the Republic of Kazakhstan is the reference point for knowledge of national history and culture, to strengthen the position of Kazakh as the state language.